(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The study of morphemes is an important step in understanding the complexity and beauty of language. Thanks to morpheme analysis, we can deepen our knowledge of words, their structure and meaning. This opens up new opportunities for us in the study of languages and their evolution.